Factors Influencing Industrialisation in Southern Africa - Johansein Rutaihwa (Business, Management and Economics: Research Progress Vol. 9, 2024)
Integrating standards, quality, accreditation, and metrology in industrialisation in Southern Africa has significant implications for the region. This ensures that Southern African industries can meet international standards and compete effectively in regional and global markets. Furthermore, it plays a crucial role in the region’s overall economic development and growth by improving productivity and cost-effectiveness, reducing waste and errors, and providing a framework for continuous industry improvement and innovation. Metrology, as the science of measurement, is fundamental to this integration and ensures the accuracy and reliability of measurements used in industrial processes.